তাজউদ্দীন আহমেদের ডায়েরি, ১৯৪৭-১৯৪৮, প্রথম খণ্ড - আহমেদ, তাজউদ্দীন, ১৯২৫-১৯৭৫. (ঢাকা : প্রতিভাস, 2009)
Diary of Tājauddina Āhamada, died 1975, prime minister of Bangladesh; autobiographical, translated from English original.
1. khaṇḍa. 1947-1948 -- 2. khaṇḍa. 1949-1950 -- 3. khaṇḍa. 1951 -- 4. khaṇḍa. 1952 -- 5. khaṇḍa. 1954
Donated By Akbar Ali Khan
In Bengali.
Keywords: Ahmed, Tajuddin, -- 1925-1975 -- Diaries; Prime ministers -- Biography -- Bangladesh; Politicians -- Biography -- Bangladesh